Basic science research opportunities in thrombosis and hemostasis: Communication from the SSC of the ISTH. (22nd April 2022) - Mutch, Nicola J.; Walters, Sam; Gardiner, Elizabeth E.; McCarty, Owen J. T.; De Meyer, Simon F.; Schroeder, Verena; Meijers, Joost C. M.
Abstract: Bleeding and thrombosis are major clinical problems with high morbidity and mortality. Treatment modalities for these diseases have improved in recent years, but there are many clinical questions remaining and a need to advance diagnosis, management, and therapeutic options. Basic research plays a fundamental role in understanding normal and disease processes, yet this sector has observed a steady decline in funding prospects thereby hindering support for studies of mechanisms of disease and therapeutic development opportunities. With the financial constraints faced by basic scientists, the ISTH organized a basic science task force (BSTF), comprising Scientific and Standardization Committee subcommittee chairs and co‐chairs, to identify research opportunities for basic science in hemostasis and thrombosis. The goal of the BSTF was to develop a set of recommended priorities to build support in the thrombosis and hemostasis community and to inform ISTH basic science programs and policy making. The BSTF identified three principal opportunity areas that were of significant overarching relevance: mechanisms causing bleeding, innate immunity and thrombosis, and venous thrombosis. Within these, five fundamental research areas were highlighted: blood rheology, platelet biogenesis, cellular contributions to thrombosis and hemostasis, structure–function protein analyses, and visualization of hemostasis. This position paper discusses the importance and relevance of these opportunities and research areas, and the rationale for their inclusion. These findings have implications for the future of fundamental research in thrombosis and hemostasis to make transformative scientific discoveries and tackle key clinical questions. This will permit better understanding, prevention, diagnosis, and treatment of hemostatic and thrombotic conditions.